Photostimulation decreases fearfulness, but improves growth performance and egg quality of breeder Pekin ducks - E.M. Oluwagbenga; J.M. Schober; M.M. Bergman; D.M. Karcher; C. Chavez; G.S. Fraley (Poultry Science)
Lighting is a critical environmental factor that influences production performance and welfare of poultry, however Pekin ducks can typically be housed under 24 h (24 h) of light. 460 hatchlings were randomly allocated to 4 rooms with two pens in each room. The rooms were allocated to 24 h light or PS. PS was achieved by gradually increasing photoperiod by half an hour per week from days 112 to 238 and held at 18 h light for the rest of life. Prior to the onset of lay, pens were organized with 30 hens and 7 drakes/pen (4 pens/treatment). We measured bodyweight at weeks 0, 1, 2, 5, 10, 19, and 29, feed intake at weeks 1 to 7 and feed conversion ratio (FCR) was calculated for weeks 1, 2, and 5. Eggs laid were recorded daily from weeks 20 to 31. Novel object test (NOT) was done at weeks 1, 5, 10, 19, and 29, transect welfare scoring at week 30, egg quality assessment at weeks 28 and 29, and fertility was determined at weeks 28 and 29. Statistical analyses were done using 2-way ANOVA, T-test, or Friedman Test with a Tukey-Kramer test as post-hoc. A p ≤ 0.05 was considered significant. Drakes bodyweight was higher in the PS compared to 24h treatment at weeks 5 (p < 0.01) and 10 (p < 0.001). No difference was observed in FCR, fertility, or transect data. NOT showed lower fear response (p < 0.05) at weeks 5 and 10 in the PS compared to 24 h treatment. The 24 h treatment increased the percent eggs laid at weeks 23 (p < 0.05), 24 (p < 0.01) and 25 (p < 0.05) compared to the PS. However, there was a higher egg weight (p < 0.001), yolk weight (p < 0.05), Haugh unit (p < 0.05), and shell weight (p = 0.05) in the PS compared to 24 h treatment. Our findings support that PS may help decrease fearfulness, improve growth performance and egg quality of breeder ducks.